Good Leadership Qualities as Expected by Industrial Employees in Samut Sakhon Province - Uthai, Prasong; Teekasap, Sombut; Khobchum, Chumphon (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2024)
The objectives of this research were 1) to study the characteristics of effective good leaders within industrial companies. in Samut Sakhon Province, 2) to study the relationship between personal factors and good leadership qualities according to employee expectations, 3) to study guidelines for personnel development to have good leadership qualities. using quantitative research The population used in the research was 717,310 employees working in industrial areas in Samut Sakhon Province. The sample group used was 400 employees by purposive random selection. Use questionnaires to collect data. analyze data by using percentage, mean, standard deviation and relationship The results of the study revealed that 1) good leadership qualities must be good, emphasizing on the first aspect, namely morality, attitude, personality, skills and knowledge. When considering in detail, it was found that the sample group had the first level of opinion, that is, able to solve immediate problems. The average was the highest level, followed by the confidence and assertiveness. 2) The relationship study found that age and ethics, age and knowledge, job position and skill, position and personality, experience and personality, experience and attitude. There was a statistical significance at the 0.05 level. And like to learn all the time. There is a process to create innovation as the key to driving the organization to create success and increase competitiveness. in Thailand alongside international competitors according to the direction of Thailand's development strategy